How does secessionism end? No-win scenarios for contemporary American secessionist movements - Pomarański, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this paper is to attempt to characterize the American secessionist movement in the 21st century. In spite of the fact that all ideas of self-determination in the U.S. are not welcomed by the federal government in Washington and as a consequence are dying on the vine, they have still reborn in subsequent separatist and secessionist initiatives. An analysis of the goals, sizes and motivations of contemporary secessionist groups in the United States will lead to the main goal of the paper, which is to answer the question about the types of strategies chosen by American secessionists in the situation of the obvious failure of their overarching political goal - independence.
Keywords: political secession in United States of America; contemporary self-determination movements